Electrical and electromagnetic geophysical prospecting for the monitoring of rock glaciers in the Dolomites, northeast Italy - Pavoni M.; Sirch F.; Boaga J. (Sensors, 2021)
The monitoring of rock glaciers plays a relevant role in relation to natural hazards in high mountain environments. Due to the climate warming, mountain permafrost is thawing, and its degradation is influencing the triggering and the evolvement of processes such as rockfalls, landslides, debris flows and floods. Therefore, the study and monitoring of these periglacial forms have both a scientific and economic importance. We tested electrical and electromagnetic measurements along the same investigation lines, in two different sites of the Dolomites area (Northeast Italy). Electrical prospecting exploits the high resistivity contrast between frozen and non-frozen debris. However, these measurements have high logistic demands, considering the complex rock glaciers surface and the need of ground galvanic contact. For this reason, we tried to compare electrical measurements with electromagnetic contactless ones, that theoretically can be used to define the distribution of electrical resistivity in the first subsoil in a quicker and easier way. The obtained results show that the joint use of the two methods allows us to characterize a rock glacier subsoil with good confi-dence. Finally, the advantages and disadvantages of both the techniques are discussed.